2015
DOI: 10.1038/ijo.2015.228
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding during the first 6 months of life, adiposity rebound and overweight/obesity at 8 years of age

Abstract: Breastfeeding during the first 6 months of life was not demonstrated to delay the age of the adiposity rebound, in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…50 The evidence surrounding breastfeeding duration and BMI rebound remains equivocal, however. 5, 14, 15 Further investigation is required to ascertain the potential influence of breastfeeding on timing of adiposity rebound.…”
Section: Discussionmentioning
confidence: 99%
“…50 The evidence surrounding breastfeeding duration and BMI rebound remains equivocal, however. 5, 14, 15 Further investigation is required to ascertain the potential influence of breastfeeding on timing of adiposity rebound.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not compatible with another study that shows the protective effect of breastfeeding on child overweight and obesity by creating a low level of insulin in serum (20) . Whereas in another study Estévez-González et al show that the percentages of children with normal weight, overweight, and obesity were similar in both groups and there were nobody mass Index differences between children with breastfeeding or without breast feeding during the first six months after delivery (21) .…”
Section: Discussionmentioning
confidence: 87%
“…Other studies that have accounted for other known childhood obesity risk factors such as SES in their analyses demonstrated no protective effect of breastfeeding (Etevez-Gonzalez et al, 2016;Victora et al 2016). Studies that did find a protective effect of breastfeeding against child obesity found that the necessary duration of breastfeeding was a minimum of 2.5 months, with a range of 2.5 months-8 months of exclusive breastfeeding necessary to produce the protective effect (Hess et al 2015;Moss and Yeaton 2014).…”
Section: Discussionmentioning
confidence: 97%